Sales Application Program at Distro X in Bekasi Web-Based - Komarudin Komarudin (Politeknik Siber Cerdika Internasional, 2021)
Information technology is growing very fast, along with human needs that are also growing, with the internet then we will get millions of information, even we can do business sales through the Internet. therefore it is necessary to use a dynamic website in the sales business as a marketing tool to increase sales. with the website will be easier in introducing its products, as well as conducting various buying and selling transactions.The purpose of this research is to produce a web-based clothing sales information system e-commerce in distro threefive, helping distro threefive in promoting and selling products to consumers. Methodology carried out in data collection related to the preparation or completion of this final task is interviews, observations and literature studies. The results of this study explain the design of the system. which includes ERD, normalization, HIPO structure, program flowchart as well as program performance design. While in the implementation there is a relationship between the table, database structure and application program used and input design (input) and output design (output).